Treatment of Extreme Tuberculous Kyphosis Using Spinal Osteotomy and Halo-Pelvic Traction: A Case Report. Issue 4 (February 2016) - Yu, Bin; Zhu, Ke; Zhao, Deng; Wang, Fei; Liang, Yijian
Abstract : Study Design: A case report of treatment of extreme tuberculous kyphosis using spinal osteotomy and halopelvic traction. Objective: The aim of this study was to describe the process and outcome of treatment of a case with extreme tuberculous kyphosis using spine osteotomy and halo-pelvic traction. Summary of Background Data: Spinal tuberculosis causes destruction, deformity, and paraplegia. Long-standing kyphosis may progress with growth in children, and produces respiratory insufficiency, and neurologic deficit. Surgery may help to prevent or reverse the neurological deterioration, while improving pulmonary function in cases with significant spinal deformity. Methods: Review of records and radiographs. Results: A 24-year-old female with tuberculous angular kyphosis presented with bilateral lower extremities paresis and dyspnea. The vertebral bodies from T3 to T9 were severely destructed, with a Cobb's angle of 180°on radiographs. The total duration of distraction using halopelvic apparatus kept 10 months. During the duration of traction, the patient underwent a posterior release surgery because flexibility of the kyphosis was not sufficient. Pedicle subtraction osteotomy and pedicle screw fixation were performed to achieve final correction when the Cobb's angle decreased to about 80°. After the whole treatment of halopelvic traction and spine ostetomy, the patient's height increased nearly 30 cm, whereas the angular kyphosis was corrected to a Cobb's angle of 30°. The patient had no complication and neurological deterioration during the treatment. Correction angle and good sagittal balance were well maintained in the duration of 2 years' follow-up. Conclusion: The halo-pelvic apparatus produces high corrective forces applied over a long period, and it provides a slow and safe correction of deformity. In cases of extreme kyphotic deformity, halopelvic traction is an appropriate technique, while avoiding many serious complications from a rapid, one-stage correction. Level of Evidence: N/A